Application progress of Traditional Chinese Medicine nursing technology in pain control after total knee arthroplasty (中医护理技术在膝关节置换术后疼痛干预中的应用进展) - LIU Fei (柳菲); YAN Qiuyan (闫秋艳) (中西医结合护理)
Total knee arthroplasty is an effective surgery in the treatment of end-stage arthritis. However, Postoperative pain adversely affects recovery and patients’ quality of life. There has been a wide use of Traditional Chinese Medicine (TCM) nursing technology in pain control after total knee arthroplasty, and common nursing interventions includes Chinese herbal medicine external application, auricular point pressing therapy, Tuina, moxibustion, and so on. Given the inadequacies in standardization of operation and evaluation system, it is required to enhance the evidence-based nursing practice and form an effective operation and evaluation system, aiming to promote the clinical practice of TCM nursing technology. (全膝关节置换术(TKA)是治疗终末期关节炎的有效方法, 但术后伤口疼痛不利于患者早期康复, 严重影响患者生活质量。中医护理技术在TKA术后疼痛中应用广泛, 且效果良好, 常见技术包括中药外用、耳穴压丸、推拿、艾灸等, 但操作频次、评价体系等尚未形成规范化、标准化, 在今后要加强循证护理实践, 形成有效的评价指标及完善的操作流程, 以推进中医护理技术的临床应用。)